Dielectric metamaterials: Fundamentals, designs, and applications - Brener, Igal; Liu, Sheng; Staude, Isabelle; Valentine, Jason; Holloway, Christopher L. (Elsevier, 2019)
Dielectric Metamaterials: Fundamentals, Designs, and Applications links fundamental Mie scattering theory with the latest dielectric metamaterial research, providing a valuable reference for new and experienced researchers in the field. The book begins with a historical, evolving overview of Mie scattering theory. Next, the authors describe how to apply Mie theory to analytically solve the scattering of electromagnetic waves by subwavelength particles. Later chapters focus on Mie resonator-based metamaterials, starting with microwaves where particles are much smaller than the free space wavelengths. In addition, several chapters focus on wave-front engineering using dielectric metasurfaces and the nonlinear optical effects, spontaneous emission manipulation, active devices, and 3D effective media using dielectric metamaterials.
CRIS-Team Scopus Importer:2023-04-20